1995
DOI: 10.2172/146730
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous biphasic extraction of uranium and thorium from contaminated soils. Final report

Abstract: Portions of this document mag be illegible ' in electronic image products. m e s are produced from the best available original dOCUIIlent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We have recently begun to scaleup ABS processes for ultrafine particle/particle separation by countercurrent extraction using a pilot-scale Karr column. 10 The physicochemical properties of aqueous polyethylene oxide) (PEO) solutions and its lower molecular weight analog, PEG, have been studied extensively and have been reviewed by Bailey and Koleske.11 A host of techniques have been used to probe the aqueous solution structure of PEO, such as light scattering,12•13 Raman spectroscopy,14 electron microscopy,15 small-angle neutron scattering,16•17 viscometry,18•19 and free volume measurements. 20 These studies have revealed many fascinating properties of aqueous PEO solutions.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently begun to scaleup ABS processes for ultrafine particle/particle separation by countercurrent extraction using a pilot-scale Karr column. 10 The physicochemical properties of aqueous polyethylene oxide) (PEO) solutions and its lower molecular weight analog, PEG, have been studied extensively and have been reviewed by Bailey and Koleske.11 A host of techniques have been used to probe the aqueous solution structure of PEO, such as light scattering,12•13 Raman spectroscopy,14 electron microscopy,15 small-angle neutron scattering,16•17 viscometry,18•19 and free volume measurements. 20 These studies have revealed many fascinating properties of aqueous PEO solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, particle size should be small enough that particle settling due to gravity is low compared to the rate of 1iquidAiquid phase separation. In general, we have found that an upper size limit of about 150-200 ym can be accommodated during continuous, countercurrent extractions (6,7).…”
Section: Introductionmentioning
confidence: 90%
“…We have been evaluating various types of ABE systems for possible applications in the treatment of solid radioactive wastes (1,2), liquid nuclear wastes (3,4), and contaminated soils (5)(6)(7), and in the removal of organics from aqueous salt solutions (8). We have also conducted fundamental studies of the solution microstructure of ABE systems using small angle neutron scattering (SANS) (9).…”
Section: Introductionmentioning
confidence: 99%